Clinical application of optical and electromagnetic navigation system in CT-guided radiofrequency ablation of lung metastases - Zenan Chen; Liangliang Meng; Yueyong Xiao; Jing Zhang; Xiaobo Zhang; Yingtian Wei; Xiaofeng He; Xin Zhang; Xiao Zhang (International Journal of Hyperthermia)
Purpose To evaluate the clinical value of CT-guided radiofrequency ablation (RFA) in the diagnosis and treatment of pulmonary metastases under optical and electromagnetic navigation.Methods Data on CT-guided radiofrequency ablation treatment of 93 metastatic lung lesions in 70 patients were retrospectively analyzed. There were 46 males and 24 females with a median age of 60.0 years (16–85 years). All lesions were ≤3cm in diameter. 57 patients were treated with 17 G radiofrequency ablation needle puncture directly ablated the lesion without biopsy, and 13 patients were treated with 16 G coaxial needle biopsy followed by radiofrequency ablation. There were 25 cases in the optical navigation group, 25 in the electromagnetic navigation group, and 20 in the non-navigation group. The navigation group was performed by primary interventionalists with less than 5 years of experience, and the non-navigation group was performed by interventionalists with more than 5 years of experience.Result All operations were successfully performed. There was no statistically significant difference in the overall distribution of follow-up results among the optical, electromagnetic, and no navigation groups. Complete ablation was achieved in 84 lesions (90.3%). 7 lesions showed incomplete ablation and were completely inactivated after repeat ablation. 2 lesions progressed locally, and one of them still had an increasing trend after repeat ablation. No serious complications occurred after the operation.Conclusions Treatment with optical and electromagnetic navigation systems by less experienced operators has similar outcomes to traditional treatments without navigational systems performed by more experienced operators.